PERANCANGAN SISTEM KONTROL OPERASI ATS BERBASIS PLC PADA SISTEM SUPLAI LISTRIK DARI PLTS, PLTB, BATERAI DAN PLN - Fakhri, Albeni; Nasir, Muhammad; Adrianti, Adrianti (Rang Teknik Journal, 2025)
This thesis discusses the design of an ATS operation control system based on PLC (Programmable Logic Controller) for an electricity supply system consisting of renewable energy sources such as Solar Power Plants (PLTS) and Wind Power Plants (PLTB), as well as batteries and conventional energy sources from PLN.This system aims to ensure efficient management and stability of electricity supply by using PLC technology, the system can be monitored and controlled automatically, allowing for real-time monitoring and fast and precise intervention when a disturbance occurs.This research contributes to the development of renewable energy systems and control technologies that can be implemented on a wider scale to improve the reliability and efficiency of the electricity supply system Keywords: PLC, PLTS, PLTB, Battery, PLN